If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6=-2(r+3)
We move all terms to the left:
6-(-2(r+3))=0
We calculate terms in parentheses: -(-2(r+3)), so:We get rid of parentheses
-2(r+3)
We multiply parentheses
-2r-6
Back to the equation:
-(-2r-6)
2r+6+6=0
We add all the numbers together, and all the variables
2r+12=0
We move all terms containing r to the left, all other terms to the right
2r=-12
r=-12/2
r=-6
| Y=18+3x^2 | | w-19/6=10 | | 4(v-2)=6v-2 | | 6k-17=55 | | |x+9|=8 | | x^2+4x-36.75=0 | | 5x-5=14x+14 | | w-82/4=3 | | s/9+91=97 | | -4(m+4)=-8 | | 245243657x=456789 | | 300=(x+15)(10+x) | | 4^2x=32^0.5 | | n-1=5+3n | | p/4+12=15 | | -2/3x+1/3=-7/6 | | 9=-7a | | x+5x-18+90=180 | | 3x=39+9 | | -1/2v-2=4 | | 18r=25 | | 600/1600=x/900 | | 4=z+15/9 | | 1600/600=900/x | | 8-b=-4 | | 9y-5y=69.96 | | 0.5(x+34.65)=37.8 | | 1/2n-3/2=-4 | | -3x^2-13x+56=0 | | 76=v/7=66 | | -78=-6d | | −8a+32=72 |